Behçet Syndrome: two cases between twins (Brazilian Journal of Health Research, 2023)
Introduction: Behçet's syndrome is an autoinflammatory systemic vasculitis of undetermined origin, predominant in Turkey with  low frequency in Western countries. Clinical manifestations involve mainly mucosa and skin, cardiovascular, nervous and gastrointestinal systems and  eyes and joints. Case Report: Two 19 years-old twins were followed up by the Infectology Service of  ‘Cassiano Antonio Moraes’ University Hospital with a diagnosis of recurrent herpes for over 8 years; Patients were then referred to the Gynecology Service for evaluation. The hypothesis of Behcet's Syndrome was raised and the diagnosis was confirmed considering the clinical symptoms and positive Pathergy test. Treatment with systemic corticosteroids was initiated, with significant significant symptoms. Conclusion: The fact that Behçet's Syndrome is rare outside Asia may raise difficulties in considering it as a differential diagnosis of other diseases. The diversity of clinical manifestations is also another factor that can delay the diagnosis.
Keywords: Behçet Syndrome; Ulcer; Twins